Web-based graph visualization system - Subramaniyam, Vinupriya (2019)
Graphs are powerful tools which provide intuitive representations of complex, interconnected data. Existing Open-Source graph visualization tools support limited functionalities and have various shortcomings in terms of performance. Graphiti aims to address these issues. Graphiti is an open source, web-based graph visualization tool created to provide seamless graph visualization. Built using JavaScript’s D3 library, Graphiti provides a rich user interface with responsive and interactive graph visualization. From loading graphs in JSON format to creating rich and colourful visualizations, Graphiti provides a range of features. It supports various interactive functions such as dragging, zooming, filtering and advanced features including the ability to run common graph algorithms on the visualizations. These comprehensive features enable better insights and understanding of the data features. This report intends to serve as a documentation of Graphiti developed as part of the author’s final year project in NTU. This report covers the various stages of the development cycle of Graphiti from Background Research and Requirements Elicitation to Implementation, Testing and Discussion.